2020
DOI: 10.1001/jamanetworkopen.2019.21036
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Mortality Associated With Orofacial Cleft Among Children in Ontario, Canada

Abstract: IMPORTANCE Orofacial cleft (OFC) is one of the most common congenital malformations, with a wide variation in incidence worldwide. However, population-based studies on the incidence of OFC in North America are lacking. OBJECTIVES To examine the incidence of OFC in Ontario, Canada, and to compare risk factors and mortality associated with children with OFC vs children without OFC. DESIGN, SETTING, AND PARTICIPANTS This population-based retrospective cohort study used health administrative data from the province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
(84 reference statements)
0
12
1
Order By: Relevance
“…Among fetal conditions, a study conducted in Brazil counts preterm birth (gestational age less than 37 weeks) before the stage of fetal weight gain, which is often associated with cesarean delivery [ 49 ]. A low-weight fetus (<1.5 kg) usually goes to post-partum mortality [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among fetal conditions, a study conducted in Brazil counts preterm birth (gestational age less than 37 weeks) before the stage of fetal weight gain, which is often associated with cesarean delivery [ 49 ]. A low-weight fetus (<1.5 kg) usually goes to post-partum mortality [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…As isolated CL was detected in only one patient and isolated CP was not detected, it can be hypothesized that this isolated malformation does not justify admission to a neonatal ICU. Higher mortality rates are also expected in neonates with CL/P when compared to neonates without this malformation (5.08 vs. 0.33 deaths in every 1,000 births per year, p<0.001) 24 . Despite these previous findings, no neonate in the present study with CL/P died before ICU discharge.…”
Section: Discussionmentioning
confidence: 92%
“…Further, clefting can occur either as isolated (non-syndromic) or as a part of a syndrome with other symptoms. OFC is caused by a combination of environmental factors (e.g., maternal illness, smoking/alcohol consumption, and malnutrition), and genetic predisposition [ 285 , 286 ]. Studies have reported an association between maternal hyperpyrexia, illnesses, and infections with the occurrence of CLP in the newborns with no gender differences [ 287 ], though the mechanism is poorly understood.…”
Section: Maternal Infections Fetal Neurogenesis and Craniofacial Defectsmentioning
confidence: 99%